Asymmetric (112¯1)[112¯6¯] twin boundary and migration mechanism in hexagonal close-packed titanium. (15th June 2022) - Li, Bin; Chen, Kefan
Abstract: Classical twinning theory predicted that a simple shear was able to create a perfect, twinned structure without the need of atomic shuffles for ( 11 2 ¯ 1 ) [ 11 2 ¯ 6 ¯ ] twinning mode in hexagonal close-packed (HCP) metals, and the elementary twinning dislocation should be a two-layer zonal. However, it was revealed in the literature that this particular twinning mode could not have mirror symmetry between the parent and twin, and shuffles should be involved during twin boundary (TB) migration. These conflicting reports indicate that the ( 11 2 ¯ 1 ) [ 11 2 ¯ 6 ¯ ] twinning mechanism has not been completely resolved, and what configuration of twinning dislocation mediates twin growth is not well understood either. In this work, atomistic simulation is conducted to further understand the twinning mechanism in titanium. Novel structural analyses are performed to reveal how the parent lattice is transformed to the twin lattice. The results show that the mirror symmetry of a perfect, unrelaxed TB breaks down after relaxation, because of the very high repulsive force between the atom pairs on mirrored positions with a spacing less than half of the lattice constant. As a result, the stacking sequence of the twin differs from that of the parent after relaxation. During twin growth, each { 1 1 ¯ 00 } prismatic plane of the parent splits into two layers and reorganize into the prismatic planes of the twin, such that the twin prismatic are no longer aligned with the parent prismatic and the mirror symmetry breaks down. This process is accomplished by atoms shuffling in the opposite direction that is perpendicular to the twinning shear. The atomic shuffles spread over multiple consecutive twinning planes to minimize the shuffling magnitude on each twinning plane. Thus, the actual TB is no longer a single twinning plane, but a multi-layer interface zone. Careful examination shows that no well-defined twinning dislocation core can be identified, although single-layer steps can still be observed. Graphical Abstract: Evolution of three prismatic columns colored in green, red and blue. The viewing direction is along the [ 11 2 ¯ 6 ¯ ], i.e. the direction of twinning shear. During twin boundary migration, each of the ( 1 1 ¯ 00 ) prismatic planes of the parent, which has a double-layered structure, splits into two layers that move in the opposite direction, and then reorganizes into the prismatic planes of the twin that are now misaligned with the prismatic planes in the parent. Image, graphical abstract